Qualitative Phytochemical Contents and Antioxidant Activity of Dammar and Stembark Extracts of Rubroshorea parvifolia (Dyer) P.S.Ashton & J.Heck. - Rosdi, Muhammad Imtiaaz Aziman; Mohd. Hassan, Norazian (Journal of Pharmacy, 2026)
Introduction: Rubroshorea species are known for their rich phytochemicals such as phenolics, flavonoids, and terpenoids in the dammar and stembark that possess antioxidant properties. The study aimed to screen the phytochemicals and evaluate the antioxidant activity of methanolic extracts from dammar and stembark of Rubroshorea parvifolia by means of 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity, total phenolic content (TPC) and total flavonoid content (TFC). Methods: Methanolic extracts of R. parvifolia dammar and stembark were prepared through maceration. Phytochemical screening was conducted to detect different classes of compounds. Antioxidant activity was initially screened by using Dot Blot assay and then quantitatively determined using DPPH radical scavenging assay. TPC and TFC were measured by using Folin-Ciocalteu method and aluminum chloride assay, respectively. Results: Phytochemical screening revealed the presence of phenolics, tannins, flavonoids, terpenoids, and triterpenoids in both extracts. Nevertheless, alkaloids and saponins were specifically detected in the dammar and stembark, respectively. The methanolic stembark extract demonstrated superior antioxidant activity with a lower half maximal inhibition concentration (IC50) value (16.52 ± 1.57 µg/mL) compared to that of dammar extract (575.68 ± 33.84 µg/mL). The activity of stembark extract is associated with its higher TPC (937.55 ± 2.40 mg GAE/g) and TFC (1016.82 ± 9.64 mg CE/g) than that of dammar extract. Conclusion: The strong antioxidant activity of methanolic stembark extract of R. parvifolia suggests its potential as natural antioxidant for pharmaceutical and nutraceutical applications. However, dammar extract, with its compelling phytochemical composition, warrants further investigation for other medicinal properties.